Low leukocyte mitochondrial DNA abundance drives atherosclerotic cardiovascular diseases: a cohort and Mendelian randomization study. Issue 4 (20th December 2022) - Luo, Jiao; Noordam, Raymond; Jukema, J Wouter; van Dijk, Ko Willems; Hägg, Sara; Grassmann, Felix; le Cessie, Saskia; van Heemst, Diana
Abstract: Aim: Mitochondrial DNA dysfunction has been implicated in the pathogenesis of cardiovascular diseases. We aimed to investigate the associations between leukocyte mitochondrial DNA (mtDNA) abundance, as a proxy of mitochondrial function, and coronary artery disease (CAD) and heart failure (HF) in a cohort study and approximate the causal nature of these relationships using Mendelian randomization (MR) in genetic studies. Methods and results: Multivariable-adjusted Cox regression analyses were conducted in 273 619 unrelated participants of European ancestry from the UK Biobank (UKB). For genetic studies, we first performed MR analyses with individual-level data from the UKB using a weighted genetic risk score (GRS); two-sample MR analyses were subsequently performed using summary-level data from the publicly available three consortia/biobank for CAD and two for HF. MR analyses were performed per database separately and results were subsequently meta-analysed using fixed-effects models. During a median follow-up of 11.8 years, restricted cubic spline Cox regression analyses showed associations between lower mtDNA abundance and higher risk of CAD and HF. Hazard ratios for participants in the lowest quintile of mtDNA abundance compared with those in the highest quintile were 1.08 (95% confidence interval: 1.03, 1.14) and 1.15 (1.05, 1.24) for CAD and HF. Genetically, no evidence was observed for a possible non-linear causal effect using individual-level weighted genetic risk scores calculated in the UKB on the study outcomes; the pooled odds ratios (95% confidence interval) from two-sample MR of genetically predicted per one-SD decrease in mtDNA abundance were 1.09 (1.03, 1.16) for CAD and 0.99 (0.92, 1.08) for HF, respectively. Conclusion: Our findings support a possible causal role of lower leukocyte mtDNA abundance in higher CAD risk, but not in HF. Graphical Abstract: Graphical abstract